Effects of weed harrowing frequency on beneficial arthropods, plants and crop yield. (23rd September 2015) - Navntoft, Søren; Kristensen, Kristian; Johnsen, Ib; Jensen, Anne‐Mette M.; Sigsgaard, Lene; Esbjerg, Peter
Abstract: Weed harrowing is an alternative to herbicides but it may have negative effects on epigaeic arthropods. We assessed the effects of frequent (four) versus two harrowings during the growing season on the density and diversity of generalist arthropods and the weed flora. Collection by flooding was used to estimate arthropod densities, after collection of weeds and crop for biomass estimation. The predatory guild of spiders Tachyporus spp. carabids was reduced by frequent harrowing. Spiders and Tachyporus spp. were the most sensitive, with up to 38% higher density in plots harrowed only twice compared with four times. Furthermore, a marginally significant decrease in arthropod diversity was found after four harrowings. The negative effect of frequent harrowing on arthropods was probably caused by a combination of direct lethal effects and habitat disruption. Additional harrowings reduced weeds with weed seed biomass, on average, being 77% higher and species diversity being 48% higher in plots harrowed only twice compared with four times. There was a positive relationship between weed biomass and predatory arthropod guild density, supporting the hypothesis that weeds promote generalist arthropod predators. Weed harrowing should be carried out early and limited to a minimum to protect flora and fauna. Frequent harrowing had no positive effect on yield, suggesting that more weeds can be tolerated to support biodiversity and biocontrol.